One for all and all for one: a review on the commonality of risk to honeybees and wild pollinators and the benefits of beekeepers in conservation - Oddie, Melissa A. Y.; Dahle, Bjørn (Frontiers in Bee Science, 2024)
Pollinator declines across the globe are centrally driven by a synergistic interaction between intensive land use, pesticides, and climate change. Competition between managed and wild pollinators has been a growing topic of research, however the ensuing social conflict builds antagonism between beekeepers and conservationists, two parties that have an interest in protecting natural diversity for pollinators. The threats perpetuating this potential for competition are as real for managed bees as wild species and uniting both groups, wherever possible, can create long lasting and meaningful change in current agricultural practices. This review examines the most recent literature on pollinator competition and the common threats that drive it. It also delves into the social elements of beekeeping and examines the potential for beekeepers to contribute to the protection of natural habitats. Beekeepers have a genuine interest to preserve natural space and with their charismatic species, dutiful observations, and innovative techniques, they can be valuable assets in filling knowledge gaps and generating public interest. Pollinator strategies in the future should include beekeepers as key stakeholders if they are to be improved.